2021
DOI: 10.1155/2021/8853056
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Review of Computer-Aided Drug Design and Its Application to COVID-19

Abstract: The recent outbreak of the deadly coronavirus disease 19 (COVID-19) pandemic poses serious health concerns around the world. The lack of approved drugs or vaccines continues to be a challenge and further necessitates the discovery of new therapeutic molecules. Computer-aided drug design has helped to expedite the drug discovery and development process by minimizing the cost and time. In this review article, we highlight two important categories of computer-aided drug design (CADD), viz., the ligand-based as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 174 publications
0
87
0
Order By: Relevance
“…Nowadays, computer-aided drug design (CADD) is a buzzword across the world to identify drug candidates from diverse sources [35]. Another tremendous screening approach is ADMET profiling, which analyses the molecular weight, lipophilicity, number of hydrogen acceptors and donors, various types of toxicity, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, computer-aided drug design (CADD) is a buzzword across the world to identify drug candidates from diverse sources [35]. Another tremendous screening approach is ADMET profiling, which analyses the molecular weight, lipophilicity, number of hydrogen acceptors and donors, various types of toxicity, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 72 reviews were identified in PubMed ® , 13 in DOAJ, 0 SciELO, and 0 Cochrane Library, with the identification of 2 reviews on related topics (one in PubMed ® and another in DOAJ, respectively) [ 5 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Immunopathologic events may contribute to explain COVID-19 pathogenesis, such as lymphopenia, neutrophilia, dysregulation of monocytes and macrophages, reduced/delayed response of type I interferon (IFN-I), antibody-dependent enhancement, and cytokine storm [ 4 ]. The knowledge of COVID-2019 immunopathology may help in the comprehension and development of new treatments and/or drug repurposing (i.e., the application of old drugs to treat new diseases) [ 5 , 6 , 7 , 8 ]. Additionally, the measurement of serum levels of pro-inflammatory cytokines (e.g., IL-6) may be applied in the management of COVID-2019 (adult and pediatric patients), such as in the assessment of risk, monitoring of disease progression, determination of prognosis, selection of therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations